The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.jaci.2004.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections in relation to age, atopy, and season of admission among children hospitalized for wheezing

Abstract: Viral infections were the dominant risk factor for wheezing among children hospitalized before 3 years of age. By comparison, a large majority of the wheezing children age 3 to 18 years had striking atopic characteristics that may be critical as a risk factor for hospitalization and an adverse response to viral infections, especially infections caused by rhinovirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
349
6
13

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(391 citation statements)
references
References 38 publications
20
349
6
13
Order By: Relevance
“…Children born in the summer and those with fall mold collection dates, an overlapping group in our study, were at an increased risk of wheeze in unadjusted logistic regression models. These observations could represent exposure to relatively high indoor fungal levels at a young age or exposure to respiratory syncytial virus or rhinovirus at an age when small airway size can be a factor in the development of wheeze during viral infection (Heymann et al, 2004;Sears and Johnston, 2007). Nonetheless, ''high levels'' of Penicillium remained a significant predictor of wheeze even after accounting for the effects of season of mold collection, the age of the baby at the sample collection date and day care attendance, a surrogate measure of respiratory infection during infancy and early childhood (Ball et al, 2000;Stark et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Children born in the summer and those with fall mold collection dates, an overlapping group in our study, were at an increased risk of wheeze in unadjusted logistic regression models. These observations could represent exposure to relatively high indoor fungal levels at a young age or exposure to respiratory syncytial virus or rhinovirus at an age when small airway size can be a factor in the development of wheeze during viral infection (Heymann et al, 2004;Sears and Johnston, 2007). Nonetheless, ''high levels'' of Penicillium remained a significant predictor of wheeze even after accounting for the effects of season of mold collection, the age of the baby at the sample collection date and day care attendance, a surrogate measure of respiratory infection during infancy and early childhood (Ball et al, 2000;Stark et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of asthma and reactive airways disease reported by parents and recorded by WITS medical personnel in the first 1-2 years life of the study subjects suggested an overuse of the diagnosis of asthma as applied to wheezing infants with respiratory syncytial virus or rhinovirus present with asthma-like symptoms (data not shown). 17,[34][35][36] Many of these young infants infected with respiratory viruses, particularly those with underlying allergies, indeed go on to have persistent asthma, but a majority have their symptoms remit in a few years. The WITS program did not provide a long-term evaluation of the persistence of asthma symptoms with measurement of pulmonary function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rhinovirus has been widely implicated in asthma exacerbations and wheezing-related hospitalizations (13,16,(23)(24)(25)(26)(27)(28)(29). Although asthma is not infectious, these aggravating viruses are infectious.…”
mentioning
confidence: 99%